Infectious profile in children with ALL during chemotherapy: A report of study group for infections. Issue 10 (October 2019) - Zawitkowska, Joanna; Drabko, Katarzyna; Szmydki-Baran, Anna; Zaucha-Prażmo, Agnieszka; Lejman, Monika; Czyżewski, Krzysztof; Zalas-Więcek, Patrycja; Gryniewicz–Kwiatkowska, Olga; Czajńska-Deptuła, Aneta; Kulicka, Elwira; Semczuk, Katarzyna; Hutnik, Łukasz; et al.
Abstract: Introduction: The treatment-related mortality in currently published studies of acute lymphoblastic leukemia (ALL) in children is 2–4%, mainly due to infections. The aim of the study was to analyse the incidence, epidemiology, profile of infection and the death rate in children with ALL. Patients and methods: The retrospective analysis included 1363 patients, aged 1–18 years, with newly diagnosed ALL, who were treated in 17 pediatric hematology centers between 2012 and 2017 in Poland. The patients received therapy according to the ALL IC-BFM 2002 and 2009 (International Berlin-Frankfurt-Munster Study Group) protocols. Results: In our study, 726 out of 1363 (53.2%) children were reported to have a microbiologically documented bacterial infection during chemotherapy. 1511 episodes of these infection were diagnosed. A total number of 251/1363 (18.4%) children experienced a viral infection. 304 episodes were documented by PCR test (polymerase chain reaction). A fungal infection was reported in 278 (20.4%) children, including 10.1% of probable, 6.0% of proven, 83% of possible diagnosis. A higher frequency of fungal infection was noted in the recent years. In our material, the rate of death was 2.4%, mainly due to fungal infection. Conclusions: Our results present the epidemiology of infectious disease in the Polish ALL patient population. The most frequent were bacterial infections, followed by fungal and viral ones. Similar to the previously published data, the mortality rate in our material was 2.4%.